Homeowners and Renters: The financial burden of housing costs in Austria - Altzinger, Wilfried; List, Emanuel (Momentum Quarterly, 2020)
This article presents an empirical analysis of the housing costs of Austrian households and the resulting financial burden for homeowners and renters. On average homeowners have significantly higher incomes than households that rent their main residence. In addition, the housing costs for homeowners are also lower in absolute terms, even if a current loan is still being paid off. Thus, the relative housing cost burden as a share of disposable income is much lower for homeowners than for renters. Consequently, the inclusion of housing costs leads to an increased inequality of disposable income (after deducting housing costs). The data also show that subsidized tenants have a comparatively lower housing cost burden than non-subsidized tenants. This finding is also confirmed by econometric exercises, which further show that housing costs represent an above-average burden for young households, singles and especially single parents. Housing policy measures designed to reduce the burden of the households most affected by high housing costs should therefore primarily focus on supporting renters.